Liquid-Liquid Extraction-Spectrophotometric Investigations of Three Ternary Complexes of Vanadium(V) - Gavazov, Kiril B.; Stefanova, Teodora S. (Croatica Chemica Acta, 2014)
Complex formation and liquid-liquid extraction (LLE) were studied in systems containing vanadium(V), 5-methyl-4-(2-thiazolylazo)resorcinol (TAO), tetrazolium salt (TZS), water and chloroform. The following three TZSs were used: 3-(4,5-dimethyl-2-thiazol)-2,5-diphenyl-2H-tetrazolium bromide (MTT), 3-(2-naphtyl)-2,5-diphenyl-2H-tetrazolium chloride (Tetrazolium violet, TV), and 2-(4-iodophenyl)-3-(4-nitrophenyl) -5-phenyl-2H-tetrazolium chloride (INT). Concentration of the reagents (TAO and TZS), pH of the aqueous medium, and shaking time were subjects of optimization experiments. Formation of ternary complexes with a composition of 2:2:2 was demonstrated by a set of different methods. Some key characteristics concerning the analytical application of the studied LLE-chromogenic systems were established as well. Keywords: solvent extraction, 4-(2-thiazolylazo)orcinol, tetrazolium salt, ion-association, 2:2:2 complex